Measuring return on investment of human resource capital : an exploratory study - Ramaswamy Nithya (2008)
The subjectivity and complexity of the value of an individual to his organization has created a hotbed of controversy among the elite in the academic fields. In recognition of these opposing views, this research is a bold step undertaken to obtain an understanding of the concept of human capital and measure the pillars supporting its construct.